ChemInform Abstract: Tandem Prins Strategy for the Synthesis of Spiropyrrolidine and Spiropiperidine Derivatives. Issue 37 (September 2015) - Reddy, Basi V. Subba; Yarlagadda, Suresh; Reddy, C. Ravikumar; Reddy, M. Rajashekhar; Sridhar, Balasubramanyan; Satyanarayana, Dayaka; Jagadeesh, Bharatam
Abstract A novel single‐step process is presented for the construction of spiropyrrolidines and spiropiperidines via cascade cyclization of amines (I) or (VIII) with aldehydes and ketones.